Association Between Connectivity of Hippocampal Sub-Regions and Auditory Verbal Hallucinations in Schizophrenia - Liu, Lin; Cui, Long-Biao; Xi, Yi-Bin; Wang, Xing-Rui; Liu, Yu-Chen; Xu, Zi-Liang; Wang, Hua-Ning; Yin, Hong; Qin, Wei (Frontiers in Neuroscience, 2019)
Background: Hippocampal dysconnectivity has been detected in schizophrenia patients with auditory verbal hallucinations. Neuroanatomical evidence has indicated distinct sub-regions in the hippocampus, but which sub-regions within the hippocampus may emerge dysfunction in the brain network, and the relationship between connection strength and the severity of this debilitating disease have yet to be revealed. Masked independent component analysis (mICA), i.e., ICA restricted to a defined region of interest, can provide insight into observing local functional connectivity in a particular brain region. We aim to map out the sub-regions in the hippocampus with dysconnectivity linked to auditory verbal hallucinations in schizophrenia. Methods: In this functional magnetic resonance imaging study of schizophrenia patients with (n = 57) and without (n = 83) auditory verbal hallucinations, and 71 healthy controls, we first examined hippocampal connectivity using mICA, and then the correlation between connection metric and clinical severity was generated. Results: As compared with patients without auditory verbal hallucinations, mICA showed a group of hyper-connections for the left middle part, as well as another group of hypo-connections for the bilateral antero-lateral and right antero-medial parts in patients with auditory verbal hallucinations. Connectivity was linked to the clinical symptoms scores in the sample of patients with auditory verbal hallucinations. Conclusions: These findings demonstrate that the left middle part is more densely connected, but the bilateral antero-lateral and right antero-medial parts are more sparsely connected in schizophrenia patients with auditory verbal hallucinations. The findings in the present study show proof of precious location in the hippocampus mediating the neural mechanism behind auditory verbal hallucinations in schizophrenia.